Perancangan Pintu Otomatis Menggunakan Sensor PIR Berbasis Arduino - Abdha Falky Rabb; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
Traditional doors usually consist of a housing or a lock and key slipper to open it. Commonly found on office or mall doors, doors can be made more practical. The door will automatically open if there is physical energy (stimulus) that moves it. For example, when someone wants to walk into the room, the door will automatically open. Doors like this are designed using automatic control using embedded system equipment. This automatic door system can be designed using automatic control combined with PIR sensors and servo motors. In terms of input equipment, a PIR (Passive Infrared Receiver) sensor is used which will detect a human approaching the door. This PIR sensor will send a signal to the Arduino process unit in which there is a microcontroller chip. This microcontroller will send the processed data to the servo motor, so that it can open or close the door automatically.